1993
DOI: 10.1038/bjc.1993.110
|View full text |Cite
|
Sign up to set email alerts
|

Use of semi-quantitative PCR for human papillomavirus DNA type 16 to identify women with high grade cervical disease in a population presenting with a mildly dyskaryotic smear report

Abstract: The natural history of squamous cancer of the uterine cervix resembles that of a sexually transmitted disease (Kessler II, 1976). Potential aetiological agents include the transforming members of the human papillomaviruses, in particular HPV types 16 and 18, since a high proportion of patients with cervical intraepithelial neoplasia (CIN) and invasive carcinoma of the cervix are infected with these HPV types (zur Hausen, 1987; Cornelisson et al., 1989). In contrast, the prevalence of HPV 16 based on rigorous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
4
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 12 publications
4
49
4
1
Order By: Relevance
“…The results were similar for all grades of cytological referral, suggesting that they may also be applicable to women with a single mildly dyskaryotic smear, and that a high level of HPV 16 in the presence of any degree of dyskaryosis is grounds for immediate referral for colposcopy. Recent results from Bavin et al (1993) also support this view. However, the lack of high levels of HPV 16 did not indicate the absence of high-grade disease, since this was found in about 40% of the CIN III patients.…”
supporting
confidence: 71%
“…The results were similar for all grades of cytological referral, suggesting that they may also be applicable to women with a single mildly dyskaryotic smear, and that a high level of HPV 16 in the presence of any degree of dyskaryosis is grounds for immediate referral for colposcopy. Recent results from Bavin et al (1993) also support this view. However, the lack of high levels of HPV 16 did not indicate the absence of high-grade disease, since this was found in about 40% of the CIN III patients.…”
supporting
confidence: 71%
“…6 In this context, it has been demonstrated for HPV 16 infections that increased viral loads would be associated with an increased risk of CIN 2 whereas reduced amounts of viral DNA reflects the absence of CIN lesions or viral clearance, which is associated with regression of CIN lesions. 7 Still, data in favor of viral load being informative for risk of CIN 2 are mainly based on HPV 16, whereas those of hrHPV types other than HPV 16 are limited and inconsistent, [8][9][10][11][12][13][14][15][16][17][18][19] obviously because of the generally low numbers of women with non-HPV 16 types studied so far. Moreover, the potential value of viral load assessment is quite likely to be dependent on the method used to define HPV positivity since its impact seems lower when the hybridization-based hybrid capture 2 (hc2) is used to define HPV positivity when compared with PCR-based assays, which generally display a higher analytical sensitivity.…”
mentioning
confidence: 99%
“…Such a policy, however, results in a high rate of colposcopic and reconisation referrals and, consequently, a Previous studies on the relation between the HPV load and the histologic grade of cervical lesions have yielded controversial results. Several investigations in which a semiquantitative PCR was used showed a significant correlation between cytological grade and the amount of HPV-16 DNA in cervical samples (Cuzick et al, 1992(Cuzick et al, , 1994Bavin et al, 1993). In contrast, two other studies using Hybrid Capture assays revealed smaller amounts of viral DNA in cervical samples of women with HSIL compared to those with LSIL (Farthing et al, 1994;Sun et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using the semiquantitative polymerase chain reaction analysis (PCR) have shown a correlation between HSIL and a large amount of HPV-16 DNA in cervical samples and a small amount in samples of a low-grade squamous intraepithelial lesion (LSIL) (Cuzick et al, 1992(Cuzick et al, , 1994Bavin et al, 1993). In contrast, two other studies using a Hybrid Capture assay revealed smaller amounts of viral DNA in the cervical samples of women with HSIL compared with LSIL (Farthing et al, 1994;Sun et al, 1995).…”
mentioning
confidence: 99%